2019
DOI: 10.5114/pjr.2019.89690
|View full text |Cite
|
Sign up to set email alerts
|

Performance of breast magnetic resonance imaging in axillary nodal staging in newly diagnosed breast cancer patients

Abstract: Purpose: To determine the diagnostic value of breast magnetic resonance imaging (MRI) in detecting axillary metastatic node in newly diagnosed breast cancer, we assessed the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of breast MRI. Material and methods: Data were collected retrospectively from January 2011 to December 2018. Preoperative breast MRI of women with newly diagnosed breast cancer were reviewed to evaluate the axillary nodal staging by using the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…In particular, breast MRI, which is widely used in the preoperative assessment of ALN status in breast cancer patients, exhibits better performance than some other techniques such as US and mammography (26). Compared with CT, MRI and PET/CT display improved sensitivity and specificity in the assessment of ALNM, with the sensitivities ranging from 47.1-98.5% and 48.1-85.7% and the specificities ranging from 57.8-98.0% and 61.5-94.7%, respectively (27)(28)(29)(30)(31)(32). However, the diagnostic accuracy of MRI and PET/CT varies depending on the study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, breast MRI, which is widely used in the preoperative assessment of ALN status in breast cancer patients, exhibits better performance than some other techniques such as US and mammography (26). Compared with CT, MRI and PET/CT display improved sensitivity and specificity in the assessment of ALNM, with the sensitivities ranging from 47.1-98.5% and 48.1-85.7% and the specificities ranging from 57.8-98.0% and 61.5-94.7%, respectively (27)(28)(29)(30)(31)(32). However, the diagnostic accuracy of MRI and PET/CT varies depending on the study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when reviewing the MRI of 99 patients, Ren et al found a specificity of 79.3% ± 5.1%, sensitivity of 92.1% ± 2.9%, PPV of 76.9% ± 4.0%, and NPV of 93.3% ± 1.9% 27 . While findings of a series of 131 patients were different, sensitivity of breast MRI for axillary nodal staging was 98.5% (95% confidence interval [CI]: 92‐100%), NPV was 96.4% (95% CI: 86.2‐99.9%), specificity of breast MRI for axillary nodal staging was 57.8% (95% CI: 44.8‐70.1%) and PPV was 71% (95% CI: 60.6‐79.9%) 28 . However, a previous meta‐analysis concluded that MRI is an effective method to differentiate metastatic ALN in BC patients with high sensitivity of 0.77 (95% CI: 0.75‐0.80) and specificity of 0.90 (95% CI 0.89‐0.91) 29 …”
Section: Discussionmentioning
confidence: 99%
“…In the daily practice of our clinic, AUS is routinely performed in the evaluation of axillary metastasis in patients with breast cancer. MRI is used to evaluate whether breast cancer is multicentric or not, and especially 18 F-FDG-PET/CT is used in the evaluation of distant metastasis. Of the 528 patients, a total of 336 patients who…”
Section: Methodsmentioning
confidence: 99%
“…The aim of our study was to evaluate the diagnostic value of axillary ultrasound (AUS), magnetic resonance imaging (MRI), and 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography ( 18 F-FDG-PET/CT) in determining ALN status in breast cancer patients with and without neoadjuvant chemotherapy compared to the golden standard of pathohistological or cytologic findings.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation